Characteristics of pantograph‐catenary arc under low air pressure and strong airflow. (27th December 2021) - Xu, Zhilei; Gao, Guoqiang; Wei, Wenfu; Yang, Zefeng; Xie, Wenhan; Dong, Keliang; Ma, Yaguang; Yang, Yan; Wu, Guangning
Abstract: Pantograph‐catenary arc fault is the primary factor threatening the stability of the power transmission for high‐speed railway. The motion characteristics of the pantograph‐catenary arc under low air pressure and strong airflow is significantly different from the case under atmospheric pressure. In this paper, an experimental platform of pantograph‐catenary arc was built to investigate arc root position‐time and arc column longitudinal drift height‐time characteristic curves under different air pressures and airflow velocites. Via analysing the corresponding results, it can be found that there are different arc root–arc column traction mechanisms at different stages of arc development. The arcing time and arc root stagnation time under low air pressure are significantly longer than the case under atmospheric pressure, resulting in more serious electrode ablation. The arc column longitudinal drift velocity and height are greater with the increase of airflow velocity. Two typical irregular arc motion phenomena—arc root jumping and arc reignition are observed. To clarify the internal mechanism of the above phenomenon, a magnetohydrodynamics (MHD) model of the pantograph‐catenary arc was lauched, the influence mechanism of the pantograph‐catenary arc temperature and voltage are studied, and the physical process of arc temperature oscillation is analysed. The research results provide theoretical support for arc protection in high‐altitude areas.